Aplikasi Penjualan Hijab Fashion - Dadi Rosadi; Nisa Rahmaniar Adilah (Jurnal Computech & Bisnis (e-Journal), 2018)
AbstractThe development of science and information technology at the present time has been more advanced and growing. This is already a lot of products from science and information technology created and used by humans at this time. These products are usually used with the aim of helping to alleviate human work and also to improve the efficiency and effectiveness of a job.A store that provides a variety of products hijab clothes or moslem clothing at an affordable price. However, the objective conditions that exist in the store in the process of marketers still use the manual system. In the process of processing sales data is still manual with written in the book sales or reports only. At the time need information about the stock of goods in the warehouse must check one by one. Therefore it takes a long time.As a solution of the existing problems in the store then the authors create a new system so that problems about data processing sales can be overcome. Keywords : Sales, Product.